2014
DOI: 10.1590/1982-0194201400032
|View full text |Cite
|
Sign up to set email alerts
|

Análise da hemorragia no parto vaginal pelos índices de eritrócitos e hematócrito

Abstract: Objective: To analyze hemorrhage at vaginal delivery using hemoglobin and hematocrit indices. Methods: This was a cross-sectional study of 328 vaginal deliveries divided into spontaneous delivery with or without episiotomy and forceps delivery. The sample was randomly stratified by type of vaginal delivery. Data were collected at admission for delivery, hospital discharge and postpartum return visit. Results: There were 122 (37.2%) deliveries without episiotomy, 147 (44.8%) with episiotomy, and 59 (18.0%) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 19 publications
0
5
0
4
Order By: Relevance
“…We think that it should be systematically adopted, to improve the recognition and early management of post-partum blood loss in low income environment and as such avoid severe PPH. Spontaneous delivery with episiotomy/perineal tear and forceps delivery can also cause a greater blood loss [37]. These relationships were not investigated in this work.…”
Section: Post-partum Hemorrhagementioning
confidence: 94%
“…We think that it should be systematically adopted, to improve the recognition and early management of post-partum blood loss in low income environment and as such avoid severe PPH. Spontaneous delivery with episiotomy/perineal tear and forceps delivery can also cause a greater blood loss [37]. These relationships were not investigated in this work.…”
Section: Post-partum Hemorrhagementioning
confidence: 94%
“…It was thus evidenced that professionals should have knowledge of the main causes of PPH, which is a determining factor for fast, efficient and resolutive assistance, thus reducing possible complications of the condition that leads many women to death. [3][4][5] It was also observed that most of the professionals had less than five years in the service and, although almost all of the interviewees were specialists in the areas of Gynecology/Obstetrics, more than half said they had never had contact with patients in the PPH, a determining factor for the quality of service. It is understood that clinical practice is the main responsible for the accumulation of knowledge and skills and such qualification does not necessarily come with the length of service in a given sector, nor with age, but with clinical experience with certain situations.…”
Section: Methodsmentioning
confidence: 99%
“…3 It is stated by some authors that, during vaginal delivery, several factors may be associated with PPH, including the third prolonged delivery period, the impediment of falling fetal presentation, episiotomy, macrosomia, use of forceps and extractor vacuum, induction and conduction of labor, previous postpartum hemorrhage and nulliparity. [3][4] By the fifth goal of the Millennium Development Goals, the World Health Organization (WHO), to the reduction of ¾ of maternal mortality in the period 1990-2015, and in order for this objective to be achieved, a reduction in maternal mortality due to PPH should occur. It is reaffirmed by the WHO that, in order to achieve this goal, it will be necessary for all to be prepared, skilled and with a careful improvement in the health of women through strategic policies and programs that ensure effective interventions for women reduction of PPH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A placenta prévia pode ter como consequência o acretismo placentário, caracterizado pela invasão excessiva do trofoblasto no miométrio, com risco de hemorragia intraparto e uso de terapêutica transfusional (GIELCHINSKY et al, 2002;PEREIRA;CAMPOS, 2013). da placenta e como última alternativa a histerectomia (MORAES et al, 2009;QUIÑONES et al, 2010).…”
Section: Introductionunclassified